12th Annual Hi-Y Conference for Older Boys at San Jose High School - Gordon, John C., 1887-1967 (photographer):::Creator:::
Group portrait of attendees for a Hi-Y conference (YMCA) at San Jose High School. Several groups of attendees are holding signs or banners that read: "Welcome to Merced," "San Francisco," "Stockton," "Stanislaus Co.," "Sacramento High School," "Reno," "Contra Costa Co.," "Y.M.C.A. Conference Club Fresno," "Tulare Co.,"Berkeley," "Humboldt County Y.M.C.A. Hi 'Y' delegation at older boys conference San Jose. Oct. 15-17-192 [illegible]. "